If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 10x + 4 Reorder the terms: -3 + 2x = 10x + 4 Reorder the terms: -3 + 2x = 4 + 10x Solving -3 + 2x = 4 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -3 + 2x + -10x = 4 + 10x + -10x Combine like terms: 2x + -10x = -8x -3 + -8x = 4 + 10x + -10x Combine like terms: 10x + -10x = 0 -3 + -8x = 4 + 0 -3 + -8x = 4 Add '3' to each side of the equation. -3 + 3 + -8x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = 4 + 3 -8x = 4 + 3 Combine like terms: 4 + 3 = 7 -8x = 7 Divide each side by '-8'. x = -0.875 Simplifying x = -0.875
| 5(p-7)-2(3-p-4)=3p | | ln(x^8)=7 | | 3*(2x-7)-(3x+3)=4*(5-2x) | | 8x/15-2x/5+3x/10-33=2x/15-x/5+5 | | x-55= | | 21-2(x-3)=48-4(3-x)-7x | | 4ab+bc=35 | | 8a+9=58 | | 3x^2+y^2=28 | | x^2=14x-15 | | 3p+5a+9=58 | | X^2-y^2-2xy=0 | | 6x-5y+2x-3y+2x= | | 8x+85=105 | | 4x^2=-100x | | 8x+3=-3x+3+11x | | 6m+m-3rpm= | | 6m+m-3rp+2rpm= | | 0=[x-(1+2i)][x-(1-2i)](x-1)(x+2) | | 0=[x-(2+3i)][x-(2-3i)](x+1)(x-2) | | -3x-11=5x+21 | | 0=[x-(2+2i)][x-(2-2i)](x+1)(x-2) | | ydx+(x+y)st=0 | | y=3x^4-4x^3-12x^2+2 | | 3.2=-6u+22.4 | | 42=4a+9 | | 7(x-8)+17=4(x-6) | | 0.7(X+20)+0.9x=78 | | 8.75=u | | -2x+2=-2(2x+5) | | 2(5x+1)=6x-(2-4x) | | 0.4(x-6)=4.0 |